Análisis sobre las actitudes, conductas y síntomas presentados en estudiantes universitarios durante la pandemia covid-19 - Páez, Maybritt (2022)
This study was aimed to analyze the attitudes, behaviour and symptoms exhibited by students from Universidad de las Fuerzas Armadas ESPE during the pandemic. The coronavirus SARS-CoV-2, known as COVID-19, was detected  for the first time in December, 2019 at Wuhan, Hubei province in China. In most cases, 80% , there were observed mild respiratory symptoms. However, there was a large percentaje of mortality at the beginning due to the lack of knowledge, prevention, and virus treatment. This research shows effects of anxiety on students because of  coronavirus (COVID-19).This meant a lifestyle change such as confinement, isolation, lock down for long periods of time, as well as other issues that students were not mentally and psychologically prepared.